Specific Density Effect of Hydraulic Oil on the Transition Process Nature in the Locomotive Multi-Circulatory Hydraulic/Mechanical Systems - A. V. Osipov; V. A. Kruchek (Вестник Научно-исследовательского института железнодорожного транспорта)
Average operating efficiency value of hydraulic/mechanical power transmission depends on the number and length of transition processes. Field investigations of hydraulic transmissions revealed that hydraulic oil temperature may vary over a wide range. Temperature variations have an impact on the hydraulic oil specific density value and as a consequence - on the parameters of the transition process occurring at the hydraulic units switching-over time. That’s why special requirements, concerning regulation of the transition processes, are imposed on the hydraulic transmission control system. They stipulate maintaining constant level of the hydraulic transmission power output. Calculations and analysis of the transition processes within the hydraulic/mechanical system at the switching-over time were performed with due regard for the hydraulic oil specific density variations. The hydraulic oil specific density influence was evaluated by the hydraulic oil temperature variations. There were considered two temperature distribution options. Temperature values in the emptied and filled hydraulic units were assumed equal for the first and different for the second option. Calculation results demonstrated that difference between the hydraulic oil specific densities in the emptied and filled hydraulic units must be maximum during the hydraulic units switching-over procedure and minimum during the switching-over procedure of hydraulic converter and hydraulic coupling. The calculation results presented in the paper allow to draw up justified upgrading recommendations of the hydraulic transmission automatic control system.